On the exploration of referenced-based super resolution for face images - Ong, Ming Yang (Nanyang Technological University, 2020)
Over the years, many people have been trying various methods to recover high-frequency image details from lower resolution images. This is mostly due to the rising demands for high-resolution images can be observed for the following fields: Medical, Astronomy and Social Media today. In this report, I will be presenting the different methods I have tested to improve Image Super-Resolution. Specialized area like Face Super-Resolution and Reference Image Super-Resolution will also be introduced and explored in this project. Extensive experiments have been performed to discover underlying reasons for the results achieved.